2008
DOI: 10.1007/s10029-008-0427-4
|View full text |Cite
|
Sign up to set email alerts
|

Amyand’s hernia in premature twins

Abstract: Amyand's hernia (AH) is the presence of a normal or inflamed vermiform appendix in an inguinal hernia sac. This condition is unusual in neonates and in infants, and it has not been described in premature twins. We present two 32-day-old biovular twins with a right AH, treated with sparing of the appendix and herniotomy. The correct management of AH is discussed via a brief review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 11 publications
0
27
0
3
Order By: Relevance
“…The reported incidence of Amyand's hernia is varied ranging from 0.19% to 1.7% of hernias, while the incidence of appendicitis occurring within an inguinal hernia is estimated at 0.07–0.13% of inflamed appendixes 3 4. The relationship between hernial incarceration and inflammation of the appendix is not clear; however, Weber et al 5 have suggested that inflammatory swelling may lead to progressive incarceration, causing impaired blood supply, ischaemia and bacterial overgrowth within the faeces-containing appendix.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of Amyand's hernia is varied ranging from 0.19% to 1.7% of hernias, while the incidence of appendicitis occurring within an inguinal hernia is estimated at 0.07–0.13% of inflamed appendixes 3 4. The relationship between hernial incarceration and inflammation of the appendix is not clear; however, Weber et al 5 have suggested that inflammatory swelling may lead to progressive incarceration, causing impaired blood supply, ischaemia and bacterial overgrowth within the faeces-containing appendix.…”
Section: Discussionmentioning
confidence: 99%
“…The appendix can be complicated by acute appendici- Figure 1 External apperance amyand's hernia in forensic autopsy: Case report and review of the Literature tis in 0.13% of cases. Often, it requires an emergent surgical treatment (4), this condition is unusual in neonates and in infants (2,3,5). However, one case of a threemonth old boy has been reported in which a right sided sliding appendiceal inguinal hernia was diagnosed preoperatively with sonography (7).This disease is often very difficult to diagnose, and most of the time it can be confused with an incarcerated or strangulated inguinal hernia (4).…”
Section: Discussionmentioning
confidence: 99%
“…Acute appendicitis in an inguinal hernia sac was referred as Amyand's hernia to honour Claudius Amyand, who was the first who described the presence of a perforated appendix within the inguinal hernial sac in 1735 (1)(2)(3)(4)(5)(6)(7). Investigation of anatomic and pathological features of this rare entity in forensic autopsy is important determinants for scientific classification, description also correct pre-postoperative managements and appropriate surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In the pediatric population, hernia repair consists mainly of high ligation of the hernia sac. Although the indications for incidental appendectomy are still present in the pediatric population, Baldassarre et al 19 argue that the appendix is beneficial for its lymphoid tissue, and its removal would be detrimental to immune development of the pediatric patient. Several authors also feel that the appendix can be useful in the future for urinary diversion or anterograde enemas.…”
Section: Appendectomy Versus No Appendectomymentioning
confidence: 98%
“…Several authors also feel that the appendix can be useful in the future for urinary diversion or anterograde enemas. [19][20][21] Advocates for appendectomy in the setting of a normal appearing appendix claim that subsequent procedures will be avoided, and the absence of the appendix will prevent future diagnostic difficulties.…”
Section: Appendectomy Versus No Appendectomymentioning
confidence: 99%